2019
DOI: 10.2147/ott.s191155
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of polymorphisms in MALAT1 with the risk of esophageal squamous cell carcinoma in a Chinese population</p>

Abstract: Objective The main aim of this study was to investigate the association of polymorphisms in long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) with the risk of esophageal squamous cell carcinoma (ESCC) in a Chinese population. Methods A total of 245 ESCC patients and 490 gender- and age-matched cancer-free controls were genotyped for four tag single nucleotide polymorphisms (SNPs) of MALAT1 (rs3200401 C > T, rs1122709 C > G, rs664589 C >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…However, rs3200401 polymorphism was associated with an increased risk of digestive cancers. Similarly, Qu et al found that rs3200401 C > T was associated with increased risk of ESCC [19]. Conversely, it had been reported that rs3200401 T allele was associated with a better survival for advanced lung adenocarcinoma patients [33].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, rs3200401 polymorphism was associated with an increased risk of digestive cancers. Similarly, Qu et al found that rs3200401 C > T was associated with increased risk of ESCC [19]. Conversely, it had been reported that rs3200401 T allele was associated with a better survival for advanced lung adenocarcinoma patients [33].…”
Section: Discussionmentioning
confidence: 96%
“…It's reported that rs664589 was associated with increased colorectal cancer susceptibility [30]. Other studies have mentioned that rs664589 polymorphisms were not associated with ESCC risk and coronary atherosclerotic heart disease [19,35]. Only a borderline signi cation was found between rs664589 polymorphism and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, increasing evidence has indicated that lncRNAs play 24 or coronary atherosclerotic heart disease. 25 We found that the MALAT1 rs664589 C>G polymorphism was significantly associated with increased endometrial cancer risk.…”
Section: Discussionmentioning
confidence: 99%